Existential Well-Being and Meaning Making in the Context of Primary Brain Tumor: Conceptualization and Implications for Intervention - Ownsworth, Tamara; Nash, Kimberley (Frontiers in Oncology, 2015)
When faced with a significant threat to life people tend to reflect more intensely upon existential issues, such as the meaning and purpose of one’s life. Brain tumor poses a serious threat to a person’s life, functioning and personhood. Although recognised as an important dimension of quality of life, existential well-being is not well understood and reflects an overlooked area of support for people with brain tumor. This perspective article reviews the historical underpinnings of the concept of existential well-being and integrates this discussion with theoretical perspectives and research on meaning making and psychological adjustment to primary brain tumor. We then provide an overview of psychosocial support interventions for people with brain tumor and describe the findings of a recently published psychotherapy trial targeting existential well-being. Overall, this article highlights the importance of assessing the existential support needs of people with brain tumor and their family members, and providing different avenues of support to facilitate the meaning making process across the illness trajectory.